Effect of Capital Structure on Financial Sustainability of Sharia Public Financing Bank (BPRS) - Titis Miranti; Ulfi Kartika Oktaviana (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2022)
The study aims to see the direct effect of capital structure on the financial sustainability of a BPRS. The second objective is to see the indirect effect of capital structure on financial sustainability with the value of profitability as a mediating variable. The population in this study were all BPRS that uploaded their financial reports through the OJK website. The results showed that the capital structure had a direct and indirect effect on the financial sustainability of a BPRS. The higher the level of capital structure, the higher the profitability, and it supports the achievement of BPRS financial sustainability